Size and ligand effects on the electrochemical and spectroelectrochemical responses of CdSe nanocrystals - Querner, Claudia; Reiss, Peter; Sadki, Said; Zagorska, Malgorzata; Pron, Adam (Physical chemistry chemical physics : PCCP, 2005)
The electrochemical properties of CdSe quantum dots with electrochemically inactive surface ligands (TOPO) have been investigated in comparison with the analogous nanocrystals containing electrochemically active oligoaniline ligands. The TOPO-capped nanocrystals have been studied in a wide size range (from 3 to 6.5 nm) with the goal to amplify the influence of the quantum confinement effect on the electrochemical response. The determined HOMO and LUMO levels have been found in good agreement with the ones obtained from photoluminescence studies and those predicted theoretically. Ligand exchange with aniline tetramer significantly influences the voltammetric peaks associated with the HOMO oxidation and the LUMO reduction of the quantum dots, which are shifted to higher and lower potentials, respectively. These shifts are interpreted in terms of the positive ligand charging which precedes the oxidation of the nanocrystals and the insulating nature of the ligand in the case of the nanocrystal reduction. The ligand-nanocrystal interactions have also been studied by UV-Vis-NIR and Raman spectroelectrochemistry in comparison with a specially prepared model compound which, apart from the anchoring function is identical to the grafted oligoaniline ligand. Both spectroelectrochemical techniques clearly indicate the same nature of the oxidation/reduction pathway for both the model compound and the grafted ligand. The influence of the grafting is manifested by a shift in the onset of the ligand oxidation as compared to the case of the "free" model compound. Since both components (ligands and nanocrystals) mutually influence their electrochemical and spectroelectrochemical properties, the newly developed system can be considered as a true molecular hybrid. Such hybrids are of interest because the potential zone of the ligand electroactivity is well separated from that of the nanocrystals and, as a result, the organic part can be electrochemically switched between the semiconducting and the conducting states with no change in the oxidation state of the nanocrystal. The newly developed system offers therefore the possibility of an electrical addressing of individual nanocrystals via the conducting ligands.